2017
DOI: 10.4103/ijmy.ijmy_177_17
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacteria in a tertiary Hospital in Portugal: A clinical review

Abstract: The present study highlights the importance of understanding the epidemiology of NTM to better comprehend their clinical impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Colonization of M. genavense in the human body is common and almost always does not result in disease; however, a case of disseminated infection has recently been published in a previously healthy pet keeper, hypothesizing the zoonotic transmission probability [ 11 ]. As a widespread family, NTM could be isolated from various specimens due to colonization or specimen contamination [ 12 , 13 ]. M. genavense has been detected more frequently in HIV patients [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colonization of M. genavense in the human body is common and almost always does not result in disease; however, a case of disseminated infection has recently been published in a previously healthy pet keeper, hypothesizing the zoonotic transmission probability [ 11 ]. As a widespread family, NTM could be isolated from various specimens due to colonization or specimen contamination [ 12 , 13 ]. M. genavense has been detected more frequently in HIV patients [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a widespread family, NTM could be isolated from various specimens due to colonization or specimen contamination [ 12 , 13 ]. M. genavense has been detected more frequently in HIV patients [ 5 , 12 ]. Despite this fact, multiple reports have discussed M. genavense infection in non-HIV immunodeficiencies, namely sarcoidosis, solid organ recipients, and primary immunodeficiencies [ 14 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then M. paragordonae was only isolated twice, both from healthcare settings [35, 36]. The NTM species more frequently isolated from patients in Portugal in the last years were those in the M. avium complex, M. gordonae and M. kansasii [37]. Interestingly, our phylogenetic study shows that the three presumptive isolates initially identified as M. gordonae based on 16S rRNA sequencing [17], are in fact members of the recently described and rarely isolated species M. paragordonae , which raises questions about the true identity of clinical M. gordonae isolates, one of the species often recovered from patients in Portugal [37].…”
Section: Discussionmentioning
confidence: 99%